PENERAPAN MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT TERHADAP HASIL BELAJAR SISWA - Sari, Oktari Rapita; Okianna, Okianna; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis study aims to determine the Influence of Implementation of Cooperative Model of Tournament Team Teams (TGT) on Student Learning Outcomes in the Materials of Class Paper Writing XI IPS SMA Negeri 1 Sungai Raya. The method used is Quasi-exsperimental (experimental pretend) with the Nonequivalent Control Group Design experiment form. In this study the experimental class is class XI IPS 1, while the control class is class XI IPS 2. Sampling is done by using a random sample technique. Data processing techniques consist of: 1. Test or test, and 2. Documentation. While the data collection tool that is: Problem test. The results showed the average symptom of the students' learning result of the experimental class and the control class. The data of the calculation result of the average of the learning result of the experimental class students is 79,09 and the mean of result of student learning control class equal to 76,50. Technique and data analysis used by t-test with error rate 5% (É‘ = 0,05) or 95% confidence level. The result of research shows that there is Influence of Implementation of Cooperative Model of Game Type Team Tournament (TGT) on Student Learning Result on Material of Paper Class XI IPS of SMA Negeri 1 Sungai RayaÂ Keywords: Tournament Team Teams (TGT) Model and Learning OutcomesÂ